The English Connection: Jacob and Johann Philipp Breyne, James Petiver and Plants: The Correspondence between the Breynes and Petiver from the 1690s - Pękacka-Falkowska, Katarzyna (Kwartalnik Historyczny, 2022)
The article discusses the hitherto unknown correspondence between the Danzig (present-day Gdańsk) botanist Jacob Breyne, his son Johann Philipp Breyne, and James Petiver in the last decade of the seventeenth century. Their correspondence documents contacts between one of the most important naturalists of the Polish-Lithuanian Commonwealth in the second half of the seventeenth century and members of the Royal Society. The content of the letters reveals how books, naturalia and various artefacts circulated between Western and East-Central Europe. It also reveals the principles of reciprocity and friendship followed by those who conducted inquiries into natural history.